PROPERTIES OF ESTIMATORS FOR CONDITIONAL SURVIVAL FUNCTIONS UNDER RANDOM CENSORING OF OBSERVATIONS FROM BOTH SIDES - Abdikalikov, Farkhad Abdizhalievich; Tadzhiev, Timur Muratovich; Erisbaev, Sabitbek Abdullaevich (SCIENCE and SOCIETY, 2026)
The article constructs a power type estimator for the conditional survival function in a regression model under random censoring from both sides. The approximation of this estimator by a sum of independent random functions and its uniform strong consistency properties are studied.